Neuroscientist's Behavioral Toolbox for Studying Episodic-Like Memory - Kunčická, Daniela; Krajčovič, Branislav; Stuchlík, Aleš; Brožka, Hana (eNeuro, 2024)
Episodic memory, the ability to recall specific events and experiences, is a cornerstone of human cognition with profound clinical implications. While animal studies have provided valuable insights into the neuronal underpinnings of episodic memory, research has largely relied on a limited subset of tasks that model only some aspects of episodic memory. In this narrative review, we provide an overview of rodent episodic-like memory tasks that expand the methodological repertoire and diversify the approaches used in episodic-like memory research. These tasks assess various aspects of human episodic memory, such as integrated what-where-when or what-where memory, source memory, free recall, temporal binding, and threshold retrieval dynamics. We review each task's general principle and consider whether alternative non-episodic mechanisms can account for the observed behavior. While our list of tasks is not exhaustive, we hope it will guide researchers in selecting models that align with their specific research objectives, leading to novel advancements and a more comprehensive understanding of mechanisms underlying specific aspects of episodic memory.
Keywords: epizodická paměť; recollection; Animals; hippocampus; episodic memory; lidé; zvířata; Neurosciences; Mental Recall; what–where–when; neurovědy; source memory; temporal binding; Memory, Episodic; rozpomínání; Humans